Diatom-derived highly branched isoprenoids in lake waters and sediments - Aaron F Diefendorf; Watts Dietrich; Hans H Naake; Thomas V Lowell; Megan C Corcoran (PANGAEA, 2025)
Diatom-derived highly branched isoprenoids (HBIs) are found extensively in marine sediments, but are observed in a limited number of lake sediments. To expand on this record, between 2022 and 2024, we collected lake surface sediment samples from 50 lakes in the United States of America from the Midwest and Northeast. Studied lakes capture a range in climate, water chemistry (e.g., pH, salinity, alkalinity), size, and trophic states. Lakes also vary in their diatom species compositions. Surface sediment samples were collected using a gravity corer or a Bolivia-type square-rod piston corer deployed from a boat. Lake sediments were extracted and analyzed for their HBI compounds and concentrations by gas chromatography mass spectrometry. Lake surface sediments were also analyzed for their carbon and nitrogen concentrations and stable isotopes. Water chemistry profiles were measured in each lake (pH, conductivity, salinity, oxidation reduction potential, dissolved oxygen) using a multiparameter sonde. Water samples from the photic zone were collected using an integrated water sampler (up to 2 m depth) and discrete samples were collected at other depths from a subset of lakes. Integrated water samples were filtered and analyzed to determine if planktonic diatoms produce HBIs. Water samples were analyzed for alkalinity, dissolved inorganic carbon (DIC) concentration, and DIC carbon isotopes.